Exploration of Physical and Mental Quality of Life Among Healthcare Professionals in Tertiary Multidisciplinary Critical Care Units: A Mixed-Methods Study - Smitha S, Smitha S; M G, Radha; T S, Deepak; Keerthi P, Keerthi P (Journal of Neonatal Surgery, 2025)
Background: Critical care units are recognized for their intense and demanding environments, placing healthcare professionals (HCPs) at significant risk for physical and emotional strain. This study explores the quality of life (QoL) in critical care nurses using validated assessment tools. Objectives: To assess the physical and mental quality of life among nurses in critical care units, identify key stressors, and explore coping mechanisms. Methods: This mixed-method study enrolled 98 critical care nurses from a tertiary care single centre ICU. SF-36 and Maslach Burnout Inventory (MBI) questionnaires was used to gather quantitative data from the nurses enrolled for the study, Descriptive statistics, analysis of variance (ANOVA), and correlation analyses were performed to explore associations between burnout, quality of life, and workplace variables. Additionally, thematic qualitative interviews were conducted to complement the quantitative findings, offering deeper insight into stressors, coping mechanisms, and professional challenges faced by ICU nurses. Measurements and Results: A total of 98 critical care nurses participated in the study, with a median age of 29 years (range 24–38), and 84% were females. Data were collected using validated tools: The Short Form-36 (SF-36) to assess physical and mental quality of life (QoL), and the Maslach Burnout Inventory (MBI) to evaluate burnout levels. Additional measures included PTSD symptoms, work satisfaction, and self-reported coping mechanisms. Assessment of quality of life (QoL) revealed that physical functioning was well preserved, with a median score of 92.9%, while emotional role functioning was impaired in 43% of participants, indicating a considerable emotional burden. Burnout was a significant concern, with 44% of nurses reporting high emotional exhaustion scores on the MBI. Although multivariate analysis did not reveal statistically significant predictors of burnout, nurses with higher job satisfaction tended to report lower levels of burnout, suggesting a potentially protective relationship. PTSD symptoms were reported by 5% of the population. Participants reported various coping strategies, including social support, mindfulness, and structured debriefing. Nurses utilizing social support strategies exhibited the lowest emotional exhaustion scores and better emotional role functioning. In contrast, those relying on non-specific or avoidant coping mechanisms tended to show higher depersonalization and reduced personal accomplishment. Conclusion: Although critical care nurses generally maintain adequate physical functioning, their emotional well-being appears significantly compromised. These findings highlight the urgent need for early, targeted interventions such as structured stress management programs, routine emotional debriefing sessions, and optimized shift scheduling to reduce burnout and enhance job satisfaction. In addition, organizational policy reforms such as the implementation of formal peer support systems and active leadership engagement are crucial in providing a supportive ICU work culture. Future research should focus on evaluating the long-term impact of these strategies on psychological resilience, workforce sustainability, and retention of skilled nursing staff in high-stress critical care environments.